Anti Korupsi Dalam Pendidikan Nasional - Riko Yohansyah Zulfahmi, Muhammad (CV. ITTC INDONESIA, 2023)
Anti-corruption education must be introduced to children from learning about life, meaning that from the start children are introduced to anti-corruption values. Corrupt behavior today is endemic in all levels. Law enforcement agencies that are deemed capable of enforcing the law are no exception to participating in corrupt behavior. Corruption has penetrated almost all sectors of national life. Communities are the victims who suffer the most. In the national education system, it is important as a basis for analyzing the application of educational theory related to educational goals, especially in relation to Pancasila values which teach anti-corruption. By the values of Pancasila, which upholds the values of truth, goodness, beauty, and religion, as well as being constructive and creative in order to be able to be responsible for advancing the Indonesian nation in adapting to the demands of a modern society based on democracy and justice and having an anti-corruption culture in the future in the life of the nation and state.